A CASE STUDY OF THE MULTICULTURAL PRACTICES OF TWO UNITED STATES DANCE EDUCATION : Implications For Indonesian K-9 Dance Education - Masunah, Juju (2008)
The purpose of this study is to identify the theories, definitions, goals, curricula, pedagogy, and practices of multicultural education, and its implications for dance education in Indonesia. Firstly, I review the literature of multicultural education theory and dance education in the United States. Secondly, I examine two dance educators and their application of multicultural education through structured and unstructured interviews, participant observations, reflective journals, and document analyses. Lastly, I consider the context of education in Indonesia and how it might be served by adapting multicultural approaches used in the United States. The findings indicate that for elementary and middle school students, the curriculum of dance education taught through a multicultural pedagogy considers students' lived experiences and dance forms from various cultures. This study concludes with a call for a multicultural dance education course to be taught in dance teacher education programs in Indonesia; a course grounded in an autobiographical method that promotes teachers' self-awareness and self-critique as they become multicultural educators and agents for change.